2018
DOI: 10.1038/s41598-018-27319-y
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-reperfusion injury and the risk of hepatocellular carcinoma recurrence after deceased donor liver transplantation

Abstract: This study aimed to evaluate the effects of ischemia-reperfusion injury (IRI) on the risk of hepatocellular carcinoma (HCC) recurrence after liver transplantation. Data of 195 patients were retrospectively analysed. Post-reperfusion aspartate (AST), alanine transaminase, and lactate dehydrogenase (LDH) levels were the primary measures of IRI. Tumour recurrence was the primary endpoint. Post-reperfusion AST was a continuous risk factor for tumour recurrence in patients within Milan criteria (p = 0.035), with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 36 publications
(38 reference statements)
4
38
0
Order By: Relevance
“…Although surgery, transcatheter arterial chemoembolization (TACE), radiofrequency ablation, radiotherapy and other therapeutic approaches can control the progress of HCC, generally speaking, HCC is still under exploration in the areas of molecular typing, molecular diagnosis and gene target selection. Although CDH 21 , LDH 22 , NCOR1 23 and other mutant genes are new biomarkers in HCC subtype classification 24,25 , identification of gene mutations that affect recurrence is complex but will have clinical significance. Meanwhile, various probability theories and linear algebra algorithms can be used for comprehensive analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgery, transcatheter arterial chemoembolization (TACE), radiofrequency ablation, radiotherapy and other therapeutic approaches can control the progress of HCC, generally speaking, HCC is still under exploration in the areas of molecular typing, molecular diagnosis and gene target selection. Although CDH 21 , LDH 22 , NCOR1 23 and other mutant genes are new biomarkers in HCC subtype classification 24,25 , identification of gene mutations that affect recurrence is complex but will have clinical significance. Meanwhile, various probability theories and linear algebra algorithms can be used for comprehensive analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of HIF and NETs formation are major responses to vascular injury during surgery, and tumor cells exposed to acute, perioperative hypoxia followed by normoxia (ischemia/reperfusion injury [I/R injury]) show increased proliferation . Also, murine models of CRC clearly demonstrated that the I/R injury accelerated the outgrowth of liver metastases …”
Section: Hypoxiamentioning
confidence: 99%
“…Ischemia-reperfusion (I/R) injury is an unavoidable consequence after liver transplantation especially at the early phase. Several lines of clinical and experimental studies have pointed out that I/R injury is a signi cant risk factor of HCC recurrence after liver transplantation (6)(7)(8). Our previous research studies have also demonstrated a positive correlation between early phase hepatic injury and late phase HCC recurrence after liver transplantation.…”
Section: Introductionmentioning
confidence: 56%
“…Despite of employing selection strategies to minimize the potential high-risk HCC patients, deciphering its underlying risk factors becomes a critical task in developing effective strategies to predict and prevent HCC recurrence (34,35). Increasing evidences from clinical and experimental research have demonstrated a positive correlation between post-transplant early phase I/R injury and late phase tumor recurrence (7,36,37). Studies have pointed out that elevated systemic and regional in ammatory responses during the early phase can increase the likelihood of late phase tumor recurrence (7,10,37,38).…”
Section: Discussionmentioning
confidence: 99%